Strategi Internalisasi Nilai BerAKHLAK untuk Penguatan Pengawasan Internal Inspektorat Setjen DPD RI - Mughny Halim, Muhammad (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: This study aims to analyze the internalization strategies of BerAKHLAK values implemented by the Inspectorate of the Secretariat General of the Regional Representative Council (DPD RI) to strengthen integrity and enhance the effectiveness of internal oversight. Methodology/approach: A qualitative intrinsic case study design was employed to explore the contextual dynamics of value internalization. Data were gathered through in-depth semi-structured interviews with eight purposively selected informants, supported by structured observations and an analysis of institutional documents. Data were analyzed using Miles and Huberman’s interactive model, which includes open coding, thematic categorization, and triangulation to ensure validity. Results/findings: The internalization of BerAKHLAK values is carried out through leadership modeling, modular training, integration into performance systems, and reflective forums. These strategies have resulted in observable changes in employee behavior, such as increased responsiveness, ethical compliance, digital literacy, and collaborative auditing. Conclusions: This study recommends implementing segmented training programs tailored to roles and tenure, formalizing behavioral performance indicators, strengthening leadership-based coaching, and establishing a sustainable monitoring mechanism to ensure effective value internalization. Limitations: This study was limited to a single organizational unit and used qualitative methods, which may limit its generalizability. Future research should adopt mixed methods and broaden the scope to multiple public institutions. Contribution: This study offers a practical and theoretical roadmap for embedding core public service values into internal audit practices, contributing to the development of value-based governance in the public sector.